Adoption of High Efficiency Irrigation Systems to Overcome Scarcity of Irrigation Water in Pakistan : Adoption of High Efficiency Irrigation Systems - Latif, Muhammad; Haider, Syed Sajjad; Rashid, Muhammad Usman (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
Water resources of Pakistan are dwindling but its water needs are continuously rising due to tremendous increase in population and urbanization. Fulfillment of increasing water demands is a challenge for the policy makers, planners, researchers as well as the end water users. Under the situation of looming water resources development in the country, efficient and economical use of existing water resources is inevitable. Unfortunately, efficiency of existing irrigation method which is predominately surface irrigation is less than 40 percent. Inadequate storage of surface water, sedimentation of existing reservoirs, falling groundwater levels, low land and water productivities are some of the major challenges of water resources in the country. The relevant literature tells that irrigation efficiency of pressurized irrigation systems, particularly of drip irrigation, is more than double the efficiency of traditional surface irrigation methods. Due to competitive water demands, it is very unlikely that in future more water will be made available to the agriculture sector. Thus agriculture is facing the challenge of ‘producing more with less water’. Climate change is further intensifying this challenge due to more variability, increased frequency and intensity of extreme hydrologic events. Under these scenarios, accelerated and sustainable adaption of pressurized irrigation especially drip irrigation must be implemented judiciously (not just experimenting as has been done in the last 4-5 decades) to fulfill future water needs as illustrated for different countries in this article. For instance, in the United States, California State which contributes about 50 percent of its total production of vegetables, fruits and nuts in addition to cereal crops. Results of a study revealed that 30 percent of the irrigators’ switched from surface irrigation (gravity) to drip irrigation from 1972 to 2001 in this state. Comparison of data for the last 3 decades in California further revealed consistent trend of decreasing use of surface irrigation and there is corresponding increase in high efficient drip irrigation. Due to water conservation and adaption of high efficiency irrigation systems (HEIS), proportion of irrigation water has reduced by 27 percent in China and 35 percent in Australia. Similarly, more examples cited in the paper also demonstrate rapid adaption of pressurized irrigation to fulfill increasing irrigation water demands. Therefore, to meet increasing irrigation demands, meticulous adaption of sustainable pressurized irrigation system is proposed along with other measures such as growing of short duration & drought resisting crop varieties, promoting water conservation and rain-water harvesting, deficit irrigation and other similar measures.